Absence of NPM1 promoter hypermethylation in human myelodysplastic syndrome. Issue 11 (5th October 2010) - Cheng, Yuen-Yee; Chau, David; Chan, Thomas; Gill, Harinder; Liang, Raymond; Kwong, Yok-Lam; Tse, Eric
Abstract : Npm1 +/− heterozygous mice develop a haematological disorder with features resembling human myelodysplastic syndrome (MDS). Promoter hypermethylation of the NPM1 gene may lead to suppressed gene transcription and hence functional haploinsufficiency, which contributes to the development of MDS. Thirty-one patients with MDS and eight normal individuals were studied for promoter methylation and mRNA expression of NPM1 . Methylation-specific PCR (MSP), COBRA and bisulfite sequencing were used to examine the NPM1 methylation status. Quantitative PCR was used to assess the expression of NPM1 . NPM1 DNA methylation was rare, occurring in one of 31 cases as determined by MSP. There was no significant difference in NPM1 mRNA expression between MDS and normal blood samples. In conclusion, the finding suggests that NPM1 methylation is rare in MDS and does not play a major role in its pathogenesis.